Penerapan Metode Earliest Due Date Pada Penjadwalan Produksi Sampel Produk Cushion Di PT XYZ - Musa, Rikan Sholikul; Azzat, Noor Nailie; Muhammad, Gunawa; Sulistyawati, Dwi Retna; Lofian, Boedi (Universitas Muhammadiyah Sorong, 2026)
PT XYZ faces delays in completing sample production of cushion products due to high sample demand and the absence of a systematic production scheduling method. This condition results in suboptimal job prioritization and delays in sample completion. Initial observations indicate that sample production delays reached up to 6 days. This study aims to implement the Earliest Due Date (EDD) method in sample production scheduling to minimize delays and improve production efficiency. The EDD method is used to determine job priority sequences based on due dates by utilizing processing time data from each production department. The implementation of the EDD method is integrated into a scheduling system based on Visual Basic for Applications (VBA) to facilitate data processing and production schedule control. The results show that the application of the EDD method is able to reduce sample completion delays from 6 days to a maximum of 4 days and decrease the level of sample production delays by 33.3%. Therefore, the EDD method is proven to be effective in improving the efficiency and accuracy of cushion sample production scheduling.